Communication, Encouragement, and Cancer Screening in Families With and Without Mutations for Hereditary Non-Polyposis Colorectal Cancer: A Pilot Study - Ersig, Anne L. (2009)
PURPOSE: Known and suspected mutation carriers for hereditary nonpolyposis colorectal cancer are advised to have colonoscopies every 1-2 years to detect colorectal cancer. Little is known about colonoscopy completion in families suspected of having hereditary non-polyposis colorectal cancer but without identified mutations. METHODS: This study examined the effect of communication and encouragement on colonoscopy in families with and without known mutations. Twenty-three respondents from 11 families with indeterminate genetic test results were matched with 23 respondents from 11 families with mutation-positive results. Hierarchical modeling examined the effects of relational characteristics on time since last colonoscopy in index cases and their first-degree relatives. RESULTS: Nearly one-fifth of respondents were not screening appropriately. Time since last screening did not differ according to family mutation status. However, respondents who communicated about risk and received encouragement to screen from a greater proportion of named family members, and those who had a greater proportion of named family members involved in both communication and encouragement were significantly more likely to have a shorter time interval since last colonoscopy. CONCLUSION: Identifying patterns of interaction within at-risk families, regardless of gene mutation status, may be one avenue for promoting screening adherence.